Faecal Bacteriome and Metabolome Profiles Associated with Decreased Mucosal Inflammatory Activity Upon Anti-TNF Therapy in Paediatric Crohn's Disease - Hurych, Jakub; Mascellani Bergo, Anna; Lerchova, Tereza; Hlinakova, Lucie; Kubat, Michal; Malcova, Hana; Cebecauerova, Dita; Schwarz, Jan; Karaskova, Eva; Hecht, Tomas; Vyhnanek, Radim; Toukalkova, Lenka; et al. (Journal of Crohn's & colitis, 2024)
BACKGROUND AND AIMS: Treatment with anti-tumour necrosis factor α antibodies [anti-TNF] changes the dysbiotic faecal bacteriome in Crohn's disease [CD]. However, it is not known whether these changes are due to decreasing mucosal inflammatory activity or whether similar bacteriome reactions might be observed in gut-healthy subjects. Therefore, we explored changes in the faecal bacteriome and metabolome upon anti-TNF administration [and therapeutic response] in children with CD and contrasted those to anti-TNF-treated children with juvenile idiopathic arthritis [JIA]. METHODS: Faecal samples collected longitudinally before and during anti-TNF therapy were analysed with regard to the bacteriome by massively parallel sequencing of the 16S rDNA [V4 region] and the faecal metabolome by 1H nuclear magnetic resonance imaging. The response to treatment by mucosal healing was assessed by the MINI index at 3 months after the treatment started. We also tested several representative gut bacterial strains for in vitro growth inhibition by infliximab. RESULTS: We analysed 530 stool samples from 121 children [CD 54, JIA 18, healthy 49]. Bacterial community composition changed on anti-TNF in CD: three members of the class Clostridia increased on anti-TNF, whereas the class Bacteroidia decreased. Among faecal metabolites, glucose and glycerol increased, whereas isoleucine and uracil decreased. Some of these changes differed by treatment response [mucosal healing] after anti-TNF. No significant changes in the bacteriome or metabolome were noted upon anti-TNF in JIA. Bacterial growth was not affected by infliximab in a disc diffusion test. CONCLUSIONS: Our findings suggest that gut mucosal healing is responsible for the bacteriome and metabolome changes observed in CD, rather than any general effect of anti-TNF.
Keywords: children; anti-TNF; Bacteria; metabolom; infliximab; Crohnova nemoc; Infliximab; dítě; Child; Metabolome; IBD; microbiome; Humans; Crohn’s disease; metabolomics; inhibitory TNF; Crohn Disease; Tumor Necrosis Factor Inhibitors; lidé